THE EFFICIENCY OF GAS-PUMPING UNITS - E. I. Kupreev; N. B. Karnitzki (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
. The reliability of the gas transmission network of the JSC “Gazprom Transgaz Belarus” depends on the efficiency of gas compressor units. Pipeline transport takes the first place among all the other ways to deliver gas because it ensures a uniform and uninterrupted supply of gas at minimum costs. The main objects of main gas pipelines include process areas, including several compressor stations and sections of the pipeline between them. Currently, a significant part of the main equipment of the gas industry is approaching its deadline of operation, which causes decrease in energy efficiency and reliability of the transmission system. At compressor plants of the JSC “Gazprom Transgaz Belarus” there are more than 4000 gas compressor units in operation including about 80% ones with gas turbine drives. It is clear that the drives of these units take a significant proportion of the pumped gas. For many years the company invests and actively participates in the creation of modern gas-pumping units practicing the wide use of conversion potential of the CIS countries. In recent years, a comprehensive approach to the assessment of the reliability and efficiency of objects of gas pipelines on the basis of mathematical modeling is actively applied. Together with the development of computer supervisory and control this opens up opportunities to improve energy efficiency in pipeline transport of gas on the basis of mathematical models and processes. The real effect obtaining is based on the actual performance of the equipment that needs to be monitored over time and to clarify.